Magnetic Susceptibility of Pumice in the Area Around Mount Singgalang, West Sumatra - Nadifa Salsabila Rifiana; Hamdi Rifai; Ciira wa Maina; Eti-mbuk Akanbi; Sándor Nagy (Frontier Advances in Applied Science and Engineering, 2025)
Mount Singgalang is a volcano that has erupted after 1600. Several types of volcanic rocks found around the Mount Singgalang area are Basalt, Andesite, Tuff Breccia, Lava Breccia, and Pumice tuff. Where, andesite and tuff pumice Mount Singgalang originated from the maninjau eruption. Pumice has several minerals, namely cristobalite, feldspar, quartz, obsidian, cristobalite, and tridymite. Pumice has one of the magnetic minerals, namely hematite (Fe2O3), but it is not known how much magnetic mineral content in it. This study aims to determine the abundance of magnetic minerals (magnetic susceptibility) in pumice around Mount Singgalang, West Sumatra. The method used is the rock magnetism method, where this method can investigate the magnetic properties of a material. The instrument used is the Bartington Magnetic Susceptibility Meter. The magnetic susceptibility value of Pumice (Pumice) in the area around Mount Singgalang, West Sumatra, where is the abundance of magnetic minerals in Pumice Rock TDK 20-02 > TDK 20-03 > TDK 20-10. The TDK 20-02 sample has a lot of superparamagnetic grains due to its low susceptibility value and high-Frequency Dependent Susceptibility, while the TDK 20-10 sample has little or almost no superparamagnetic grains due to the high susceptibility value and low-Frequency Dependent Susceptibility.